Advancement of Eye Health Services by Adopting Peek Solution in Province of Sindh - Memon, Shahzad; Sher Wali, Fariha; Hassan, Ahdi; Iqbal Haroon, Mohsin; Ali Surhio, Waqas; Rajper, Jalil Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In Sindh, the Sindh Institute of Ophthalmology & Visual Sciences (SIOVS) has launched PEEK (Portable eye examination kit) Vision Project in collaboration with Christoffel Blinden mission (CBM). This is to be viewed as a beacon of hope for the patients grappling with eye health issues. The project is related with comprehensive eye care services, ranging from primary to tertiary ophthalmological healthcare systems. This article explains the potential profound impact of the Peek Vision project on the eye health landscape, specifically in Sindh. Peek technology is clinical testified for eye healthcare. Aim: To reduce the prevalence of avoidable blindness. Methods: The study performed through PEEK technology, including three community, household and school components to access the gap of referred patients. Screening activities conducted by 21 lady health visitors, 17 lady health supervisors, 401 lady health workers, and 20 teachers trained through PEEK technology for eye conditions. Result: The findings highlighted the transformative potential of PEEK technology in advancing primary eye health care, offering a viable solution to global health challenges. The results analysed the understandable use of utilizing technology to achieve a fair eye health for everyone, offering insights for forthcoming research, policy formulation, and healthcare strategies in this pivotal domain.